Garden of evil [videorecording (DVD)] - Hathaway, Henry, 1898-1985; Cooper, Gary, 1901-1961; Hayward, Susan, 1917-1975; Widmark, Richard (20th Century Fox Home Entertainment, 2008)
When a ship carrying three American fortune hunters strands them in Mexico, fate deals them a great hand - from the bottom of the deck. In exchange for a fat payday, they must journey into the heart of evil to rescue a trapped miner. With death surrounding them and murderous Apache warriors at their heels, it will take all their cunning, ingenuity and bravery to excape with their reward, as well as their lives.